2015
DOI: 10.1007/s11207-015-0759-z
|View full text |Cite
|
Sign up to set email alerts
|

Corotating Interaction Regions as Seen by the STEREO Heliospheric Imagers 2007 – 2010

Abstract: NASA's Solar Terrestrial Relations Observatory (STEREO) mission has coincided with a pronounced solar minimum. This allowed for easier detection of corotating interaction regions (CIRs). CIRs are formed by the interaction between fast and slow solarwind streams ejected from source regions on the solar surface that rotate with the Sun. High-density plasma blobs that have become entrained at the stream interface can be tracked out to large elongations in data from the Heliospheric Imager (HI) instruments onboard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…CDSs are most clearly imaged in the heliosphere during solar minimum, when the heliospheric images are not too perturbed by the presence of CMEs (Figure 3). Their derived speeds correspond to that of the slow solar wind throughout the solar cycle (Figure 2; see also Conlon et al (2015)). This is in good agreement with the results of analysis of their source regions using a PFSS model, if we relate large expansion factors to slow solar wind speeds (Figure 11) as is commonly done (Wang and Sheeley, 1992;Arge et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…CDSs are most clearly imaged in the heliosphere during solar minimum, when the heliospheric images are not too perturbed by the presence of CMEs (Figure 3). Their derived speeds correspond to that of the slow solar wind throughout the solar cycle (Figure 2; see also Conlon et al (2015)). This is in good agreement with the results of analysis of their source regions using a PFSS model, if we relate large expansion factors to slow solar wind speeds (Figure 11) as is commonly done (Wang and Sheeley, 1992;Arge et al, 2002).…”
Section: Discussionsupporting
confidence: 54%
“…We have also found that the predicted arrival time of these structures at 1 AU has an accuracy of about 9 hours for ST-A and 11 hours for ST-B. Since the completion of this work, a paper by Conlon et al (2015) has been published, which studies a smaller sample of 40 CDSs (although obviously they did not use that terminology) also observed in ecliptic J-maps from HI on ST-A between 2007 and 2010. Those authors come to similar conclusions about the propagation speed of CDSs detected by HI being close to the slow solar wind speed.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Rouillard et al (2008) showed that plasma parcels entrained into corotation interaction regions (CIRs) could be imaged in HI. Subsequently, Plotnikov et al (2016) tracked many such events in HI images to study the long-term variability of CIRs and whether their arrival at Earth could be predicted from analysis of the HI images, demonstrating that they typically propagate at close to the slow solar wind speed ahead of the CIR, and their arrival near Earth can be predicted with an accuracy of several hours; these results broadly consolidate those from similar but independent studies by Davis et al (2012) and Conlon et al (2015). This line of research was further pursued by Sanchez-Diaz et al (2017), who better quantified the temporal and spatial scales of plasma blobs released into the heliosphere near the heliospheric current sheet.…”
Section: 1029/2019sw002226supporting
confidence: 62%
“…It is now known that CIRs produce an easily recognized signature, particularly in STEREO A imaging data, as the location of the spacecraft to the west of the Sun‐Earth line placed it in a favorable location to observe the developed CIR front far from the Sun, prior to its arrival at Earth [see, e.g., Rouillard et al , ; Tappin and Howard , ; Wood et al , ]. These characteristic CIR signatures appear in a type of representation of SECCHI data known as a “J‐map” [ Davies et al , ], where a lateral slice through an image data cube produces a map of brightness as a function of elongation and time [see Rouillard et al ,, ; Tappin and Howard , ; Conlon et al , for some examples of J‐maps of CIRs]. This has provided a new capability to predict CIR arrivals ahead of their arrival at 1 AU, as workers can observe the development of these signatures in the J‐map hours, and potentially days, ahead of their arrival at 1 AU [e.g., Davis et al , ].…”
Section: Polarization Properties Of Thomson Scattered Lightmentioning
confidence: 99%